PENDIDIKAN POLITIK DAN PEMBENTUKAN KELOMPOK PENGAWAS DANA DESA - Faqih Alfian; taufik akbar (Jurnal Abadimas Adi Buana, 2019)
Education is one means for transferring knowledge. With a variety of media used, it is expected to be able to provide the expected information. Political education is one of them, with the hope that people understand and understand what is meant by politics. Especially in rural communities where the tendency to have minimal information about politics. In this activity, political education uses the andragogy method, where learning is specifically for adults. Invite the community to play an active role in the problems that exist. Focus Group Discussion is one vehicle for community involvement, they can express their opinions. The main target in this activity is the youth group. The results of service are: 1. The implementation of "Political Education and Establishment of Village Fund Supervisory Groups" departs from two things, namely the first concerning the urgency of community participation in village governance. Second, departing from concerns about the tendency of community apathy in managing village funds, 2. The process of organizing this service is carried out by the andragogy method in which participants are stimulated through group discussions, and are also given the opportunity to express their opinions during the course of thematerial. is when initiating the formation of a superv isory group, they carefully observe it, and are very enthusiastic in discussing how the oversight mechanism will be carried out.